Salivary Biomarkers Associated With Gingivitis and Response to Therapy - Syndergaard, Ben (J Periodontol, 2014)
BACKGROUND: Salivary biomarkers are potentially important for determining the presence, risk, and progression of periodontal disease. However, clinical translation of biomarker technology from lab to chairside requires studies that identify biomarkers associated with the transitional phase between health and periodontal disease (i.e., gingivitis). METHODS: Eighty participants (40 with gingivitis, 40 healthy) provided saliva at baseline and 7 to 30 days later. An additional sample was collected from gingivitis participants 10 to 30 days after dental prophylaxis. Clinical parameters of gingival disease were recorded at baseline and the final visit. Salivary concentrations of interleukin (IL)-1β, IL-6, matrix metalloproteinase (MMP)-8, macrophage inflammatory protein (MIP)-1α, and prostaglandin E(2) (PGE(2)) were measured. RESULTS: Clinical features of health and gingivitis were stable at both baseline visits. Participants with gingivitis demonstrated significantly higher bleeding on probing (BOP), plaque index (PI), and gingival index (GI) (P ≤ 0.002) and a significant drop in BOP, PI, and GI post-treatment (P ≤ 0.001). Concentrations of MIP-1α and PGE(2) were significantly higher (2.8 times) in the gingivitis group than the healthy group (P ≤ 0.02). After dental prophylaxis, mean biomarker concentrations did not decrease significantly from baseline in the gingivitis group, although concentrations of IL-1β, IL-6, and MMP-8 approached healthy levels, whereas MIP-1α and PGE(2) concentrations remained significantly higher than in the healthy group (P ≤ 0.04). Odds ratio analyses showed that PGE(2) concentrations, alone and in combination with MIP-1α, readily discriminated gingivitis from health. CONCLUSIONS: Salivary PGE(2) and MIP-1α discriminate gingivitis from health, and patients with gingivitis who return to clinical health continue to produce inflammatory mediators for weeks after dental prophylaxis.